(untitled) (Marketing Jurnali, 2025)
This article explored the theoretical foundations, practical conditions, and development prospects of digital marketing within small business entities. Modern digital marketing tools — including social media marketing, SEO, email marketing, and content marketing — were examined in relation to their effectiveness in improving marketing performance among small businesses. The study employed theoretical analysis based on scientific literature and Uzbekistan’s legal framework, alongside empirical observation and SWOT analysis to identify existing c hallenges and propose strategic solutions. The findings demonstrated that the implementation of digital marketing significantly contributed to brand awareness, customer base expansion, and increased sales volumes in small businesses. However, key barriers such as low digital literacy, limited finan cial resources, and underdeveloped infrastructure were also identified. As a result, practical recommendations were proposed, including improving technological readiness, enhancing governmental support, and simplifying access to innovative digital platform s for small business entities.